Advances in theory and practice of computational mechanics : proceedings of the 21st International Conference on Computational Mechanics and Modern Applied Software Systems /: proceedings of the 21st International Conference on Computational Mechanics and Modern Applied Software Systems. (©2020) - Unknown
No abstract available